Ionothermal Synthesis in an Ionic Liquid and Crystal Structure of [C4H12N2] [CoCl4]. (August 2016) - Sun, Taifan; Feng, Shide; Lu, Bin; Cai, Qinghai
The compound [C4 H12 N2 ][CoCl4 ] was ionothermally synthesised in an ionic liquid medium and shown by X-ray single crystal diffraction analysis to consist of four piperazinium C4 H12 N2 2+ cations and four CoCl4 2- complex anions. Thermogravimetric analysis indicated that [C4 H12 N2 ][CoCl4 ] possesses good thermal stability below 320 °C.